2022
DOI: 10.1021/acs.jpcc.2c01099
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Probe of Aminopolymer Mobility in Bulk and in Nanoconfined Direct Air CO2 Capture Supports

Abstract: Poly(ethylenimine) (PEI) is widely recognized as an efficient carbon capture medium. When loaded onto mesoporous oxide supports, the polymer becomes particularly attractive for direct air capture (DAC) applications given the high surface area of the composites, the low volatility of the polymer, and the excellent cyclability of the system. As polymer segmental mobility is coupled with CO 2 uptake and diffusion, understanding how that mobility is influenced by nanoconfinement will ultimately be critical to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 70 publications
1
27
0
Order By: Relevance
“…We previously detailed the merits of employing fluorescent probes based on tetraphenylethylene (TPE) in a proof-of-concept study for qualitatively comparing aminopolymer mobility across confined mesoporous DAC composites. 35 Here, we develop these probes further to study branched PEI mobility in model DAC systems as a function of real-world operating conditions, beginning with moisture uptake as a function of RH exposure. PEI composites with γ-Al 2 O 3 are quite hygroscopic; 24 a composite that is 40 wt % PEI can uptake as much 1.7 equivalents in weight of water relative to PEI when allowed to equilibrate in a stream of humid N 2 (vide inf ra).…”
Section: The Journal Of Physical Chemistry Cmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously detailed the merits of employing fluorescent probes based on tetraphenylethylene (TPE) in a proof-of-concept study for qualitatively comparing aminopolymer mobility across confined mesoporous DAC composites. 35 Here, we develop these probes further to study branched PEI mobility in model DAC systems as a function of real-world operating conditions, beginning with moisture uptake as a function of RH exposure. PEI composites with γ-Al 2 O 3 are quite hygroscopic; 24 a composite that is 40 wt % PEI can uptake as much 1.7 equivalents in weight of water relative to PEI when allowed to equilibrate in a stream of humid N 2 (vide inf ra).…”
Section: The Journal Of Physical Chemistry Cmentioning
confidence: 99%
“…Correll et al recently demonstrated that THPE emits near 460 nm and appears blue in a frozen/glassy/ aggregated state, while it appears green and emits closer to 530 nm in a viscous PEI solution. 35 While TPE derivatives are much more commonly employed as AIE rather than ratiometric probes, that initial work demonstrated how a ratiometric analysis of the emission of THPE could be used to accurately assess aminopolymer and small-molecule melting points and glass transitions. The efficacy of the probe was benchmarked in 12 systems with melting points spanning ∼200 °C, both in the bulk and in confined mesoporous oxides.…”
Section: The Journal Of Physical Chemistry Cmentioning
confidence: 99%
See 1 more Smart Citation
“…), the dynamic motions of the confined amines and their relationship with CO 2 uptake kinetics and capacity remain relatively poorly understood. [23][24][25]35 A primary challenge with quantifying the mobilities and structures of the amine compounds is the difficulty in characterizing their structures and morphologies due to their confinement in the porous support. Examples from the literature include a report characterizing PEI mobility under confinement in SBA-15 silica by quasielastic neutron scattering (QENS) 24 and a study probing CO 2 diffusivity within PEI/ amorphous silica sorbents via FTIR studies.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For instance, amines buried toward the pore walls are not as effective in capturing CO 2 as amines farther from the pore walls due to diffusive barriers. ,, Although the impact of the chemical structure of supported amines has been well-correlated with CO 2 uptake performance on the molecular level (e.g., the role of primary, secondary, tertiary amines; the role of accessible vs sterically hindered amines, etc. ), the dynamic motions of the confined amines and their relationship with CO 2 uptake kinetics and capacity remain relatively poorly understood. , …”
Section: Introductionmentioning
confidence: 99%